An Empirical Review of Extraction Bolting Design in Deep Ore Zone Mine PT Freeport Indonesia - E Widijanto; F Sinaga (The Australasian Institute of Mining and Metallurgy, 2002)
PT Freeport IndonesiaÆs Deep Ore Zone (DOZ) mine is the new underground block caving mine within the East Ertsberg Skarn System (EESS) which started production in mid-2000. The DOZ will produce 25 000 tpd using mechanised block cave mining method and will be the fourth underground mine opened within the EESS deposit. A review of the DOZ extraction bolting design was conducted in November 2000. The aim of this review was to re-evaluate the effectiveness of the current design in relation to bolt length and spacing and to challenge some questions about the technical background of the design. For instance, the influence of the rock condition on the design. To review this bolting design, several books and papers are reviewed and several experienced people have been contacted to give their opinion. The methodology used for this review is:reviewing the technical background of current design; collecting ideas and alternatives; collecting data from books and personal communication and conducting analysis; and conclusion and proposed design.